The Effect of Economic Recovery Budget Efficiency on Price Stability in Indonesia: The Moderating Effect of Covid-19 Fluctuations - KUSUMAWARDHANI, ANDINI; FAJRI, MOH. NAJIKHUL (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
People's purchasing power are dropped during the coronavirus disease 2019 (COVID-19) pandemic resulting in deflation. This condition will aggravate the macroeconomic performance and economic activity of the community. The government as an economic stabilizer must take appropriate steps to create a good economic climate. On this basis, this study was formulated to review the technical efficiency of the social and economic recovery safety policy on price level movements during the COVID-19 period. This study uses efficiency analysis: Data Envelopment Analysis and Regression of short-term OLS-Estimator (STEOLSE) which involves all components of the social-economic recovery budget, inflation, economic uncertainty, economic policy uncertainty, and COVID-19 fluctuations. The results suggest that the technical efficiency of the social-economic recovery policy in the previous period will lead to a decrease in the price level. Meanwhile, the increase in COVID-19 cases caused prolonged deflation. This indicates that good budget absorption will be followed by an increase in people's purchasing power. However, the increase in COVID-19 cases will encourage people to continue to practice social distancing so that consumption activities are also disrupted.